Enhance multipath routing in topology transparent network for better QoS in MANET (International Journal of Engineering and Computer Science, 2016)
the interconnected nodes in wireless environment are forming a dynamic, temporary and open network called Mobile Ad hoc Network (MANET). In Mobile ad hoc networks communication are not very easy because of limited available bandwidth. The network performance is also being possible to measures by Quality of Service (QoS). The QoS measures through criteria of modification in routing strategy, improvement in packets dropping and all the criteria that change the network parameters for improving performance. Conventionally, every network protocols follow the criteria of strictly layered structure and implement congestion control, routing and scheduling independently at different layers. In this paper we research for control congestion and collision in dynamic network. In term of lesser congestion and collision QoS of routing with multipath protocol is measures. In this research the three scenarios of routing is considered. In first scenario the normal performance of ad hoc one demand multiple distance vector routing protocol (AOMDV) is measures, second one is measures on the basis of unassigned slots utilization to senders and third is shows the enhancement by adding them the concept of location based routing and queue estimation approach. The multipath routing protocol in MANET has the capability of balance the load in network properly by providing the alternative paths possibility. The proposed scheduling techniques is reducing the bandwidth consumption and possible to handle the problem of congestion and collision i.e. necessary for improving the QoS of routing in dynamic network. The simulation results are shows that the proposed performance is better than the existing approaches.